2019
DOI: 10.1182/blood-2019-126286
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing Results of a Phase 1B/2 Dose-Escalation and Cohort-Expansion Study of the Selective, Noncovalent, Reversible Bruton'S Tyrosine Kinase Inhibitor, Vecabrutinib, in B-Cell Malignancies

Abstract: Background: Vecabrutinib is a selective, reversible, noncovalent BTK inhibitor (BTKi) with potent in vitro inhibitory activity against both wild type and C481S-mutated BTK, the most common mutation detected in patients (pts) with CLL relapsing on treatment with covalent BTKi (cBTKi). Methods: This is an open-label, modified 3+3 dose-escalation, cohort expansion phase 1b/2 trial to evaluate safety, pharmacokinetics (PK), pharmacodynamics (PD), maximum tolerated dose (MTD) and antitumor activity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…A phase Ib/II dose-escalation and cohort-expansion study is ongoing in patients with relapsed/refractory advanced B cell malignancies who progressed on covalent BTK inhibitor therapy. According to the reported data, 27 patients (CLL, n = 21; MCL, n = 2; WM, n = 3; MZL = 1) have been treated with doses ranging from 25 to 300 mg, twice daily [ 48 ]. The maximum tolerated dose (MTD) has not been reached.…”
Section: Non-covalent Btk Inhibitors In B Cell Malignanciesmentioning
confidence: 99%
See 2 more Smart Citations
“…A phase Ib/II dose-escalation and cohort-expansion study is ongoing in patients with relapsed/refractory advanced B cell malignancies who progressed on covalent BTK inhibitor therapy. According to the reported data, 27 patients (CLL, n = 21; MCL, n = 2; WM, n = 3; MZL = 1) have been treated with doses ranging from 25 to 300 mg, twice daily [ 48 ]. The maximum tolerated dose (MTD) has not been reached.…”
Section: Non-covalent Btk Inhibitors In B Cell Malignanciesmentioning
confidence: 99%
“…The maximum tolerated dose (MTD) has not been reached. Data regarding safety are available for 24 patients; the most frequent AEs included anemia (37.5%), neutropenia (25%), night sweats (25%), and headache (25%) [ 48 ]. Grade 3 drug-related AEs included alanine aminotransferase (ALT) elevation, neutropenia and worsening anemia (all in 1 patient), and leukocytosis (2 patients).…”
Section: Non-covalent Btk Inhibitors In B Cell Malignanciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to ibrutinib, an irreversible, covalent BTKi, is mediated by an acquired cysteine-to-serine mutation in BTK. 37,38 Reversible, noncovalent BTKis, including GDC-0853, 39 LOXO-305, 40 ARQ 531, 41 and vecabrutinib, 42 may overcome BTKi resistance. Although trials of noncovalent BTKis are ongoing and in early phases, preliminary data suggest that these agents have clinical activity in heavily pretreated populations; however, the exact number of patients who have received previous treatment with venetoclax is not reported.…”
Section: Noncovalent Btkis After Venetoclaxmentioning
confidence: 99%
“…Although trials of noncovalent BTKis are ongoing and in early phases, preliminary data suggest that these agents have clinical activity in heavily pretreated populations; however, the exact number of patients who have received previous treatment with venetoclax is not reported. [40][41][42] In the preliminary results from the phase 1 dose-escalation trial of LOXO-305, there was a reported response to the noncovalent BTK in an R/R CLL patient who had an acquired BCL2 Gly101Val mutation after venetoclax therapy. 40…”
Section: Noncovalent Btkis After Venetoclaxmentioning
confidence: 99%